Determination of Servant Leadership on Worker Performance Mediated by the Quality of Work -Life and Moderated by Work Engagement - Junita, Audia; Nahrisah, Ezzah; Oktaviani, Herdinda (JDM (Jurnal Dinamika Manajemen), 2022)
Worker performance is volatile and does not just appear. Good worker performance is stimulated by various organizational and individual factors. The research objectives to analyze the impact of serv- ant leadership on worker performance mediated by the quality of work-life and moderated by work engagement. This research is an explanatory type. All staff of PT Alamjaya Wirasentosa as many as 134 people became the population and sample. Saturated sampling are used in determining the re- search sample. The analytical technique used causal step mediation test and the absolute difference value moderating test. The results prove that servant leadership has a significant positive impact on employee engagement mediated by the quality of work-life. Servant leadership has a significant nega- tive impact on employee engagement moderated by work engagement. In this case, work engage- ment weakens the impact of servant leadership on worker performance. Further research needs to be done on a larger sample size by exploring variables that can strengthen the influence of servant leadership in improving employee performance to contribute to the organization’s competitive ad- vantage.